Lithium phosphonate umpolung catalysts: Do fluoro substituents increase the catalytic activity? - Gliga, Anca; Goldfuss, Bernd; Neudörfl, Jörg M. (Beilstein Journal of Organic Chemistry, 2011)
Fluorinated and nonfluorinated phosphonates are employed as precatalysts in lithium phosphonate catalyzed cross benzoin couplings. Surprisingly, a decreased catalytic activity for the fluorinated precatalysts compared to the nonfluorinated systems is observed. Furthermore, the ring size of six, seven and nine membered ring catalysts appears not to be crucial for their catalytic activity.
Keywords: benzoin coupling; catalytic activity; fluoro effects; lithium phosphonates; umpolung